The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1103/physrevd.102.074014
|View full text |Cite
|
Sign up to set email alerts
|

Top quark pair production in the exclusive processes at the LHC

Abstract: We analyze the LHC prospects for measurements of the tt pair produced exclusively in photon-photon or semiexclusively in photon-Pomeron and Pomeron-Pomeron processes using protons tagged in forward proton detectors on both sides of the interaction point. These processes are interesting from the point of view of a possible measurement of the top quark mass and constraining models used in beyond the Standard Model physics. Focusing on the semileptonic channel, tt → jjblν lb , making use of the exclusive nature o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 50 publications
0
38
1
Order By: Relevance
“…The predictions of forward proton scattering arise in a diverse range of physics, including the hard [1,2] and nonperturbative QCD [3], interactions at electroweak scale [4][5][6][7], and searches for physics beyond Standard Model [8][9][10][11][12][13]. Such events, usually called diffractive, involve an exchange of a colourless object between interacting protons, one or both of which may remain intact.…”
Section: Studies Of Diffractive Physics With Afpmentioning
confidence: 99%
“…The predictions of forward proton scattering arise in a diverse range of physics, including the hard [1,2] and nonperturbative QCD [3], interactions at electroweak scale [4][5][6][7], and searches for physics beyond Standard Model [8][9][10][11][12][13]. Such events, usually called diffractive, involve an exchange of a colourless object between interacting protons, one or both of which may remain intact.…”
Section: Studies Of Diffractive Physics With Afpmentioning
confidence: 99%
“…An alternative, recently proposed in Ref. [1] (see also Ref. [10]), is the study of top quark production in pp collisions characterized by intact protons in the final state.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous article [1], we have performed the first comprehensive study of the elastic top quark for all luminosity scenarios considered, although a good separation between the two is observed for rather low amounts of pile-up, typically lower than 50. In particular in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous phenomenology studies based on the use of the proton tagging technique to study two-photon fusion interactions can be found in refs. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Other interesting studies that aim also to describe photon fluxes in processes with proton dissociation, treated in the k T factorization framework, are presented in refs.…”
Section: Introductionmentioning
confidence: 99%